Factors associated with diagnostic delay in children with Wilms’ tumor - Gutierrez, Francisca Norma; Aguiar Moraes, Guilherme de; Grabois, Marilia Fornaciari; Ferman, Sima Ester; Moraes Barbosa, Adauto Dutra (Journal of Advanced Pediatrics and Child Health, 2021)
Background: In Wilms’ tumor, the time elapsed between clinical diagnosis and the start of treatment is clearly associated with morbidity and mortality. As treatment delay can influence patient survival, identification of possible causes can mitigate the consequences arising from prolonged diagnostic uncertainty. Objective: To ascertain whether an initial diagnosis of Wilms’ tumor in the emergency department influences patient prognosis depending on the type of referral for definitive treatment. Patients and methods: Retrospective chart review of 98 children receiving treatment for Wilms’ tumor at the Brazilian National Cancer Institute (INCA) between April 2003 and December 2016. Patients were categorized into two groups: those referred directly from an emergency public department to INCA and those first transferred to another hospital before being referred to INCA. Results: Of the 98 cases included in the study, 42.9% were direct referrals and 57.1% were indirect referrals. Presence of an abdominal mass was the most common presenting complaint, followed by abdominal pain. In cases with larger tumors, the mean tumor volume was greater than reported elsewhere in the literature, suggesting longer disease duration. Significantly higher tumor volumes were observed in patients with a palpable abdominal mass as compared to those with the second most frequent complaint (abdominal pain). Conclusion: The findings of this study support the hypothesis that patients diagnosed with kidney masses in the emergency department are at greater risk of delayed diagnosis when they are referred first to a non-specialized outside hospital than when referred directly to a specialized cancer treatment unit.